Psychological well-being among Working Women: A Systematic Review - Dewita Nur Wulandari; Tulus Winarsunu; Nida Hasanati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Working adult women face multiple role demands that may affect their psychological well-being. This systematic review aims to examine factors influencing Psychological well-being among working women using a systematic literature review (SLR) approach guided by PRISMA. The literature search identified 302 articles, which were screened to obtain 21 eligible studies. The findings indicate that Psychological well-being is influenced by individual factors (self-compassion and resilience), work-related factors (workload, job satisfaction, and organizational support), as well as social and contextual factors (social support, work-life balance, and changes in work systems). This finding confirms that the Psychological well-being of working women is a multidimensional construct that is influenced by the interaction of internal and external factors, thus requiring an integrative approach in efforts to improve psychological well-being.